2008
DOI: 10.1016/j.enpol.2007.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of daylight saving time on lighting energy use: A literature review

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 15 publications
3
44
0
3
Order By: Relevance
“…2 Since fatal crashes are more prevalent in the evening (online Appendix Figure A-1), it is possible that transferring light from a lower risk morning period to a higher risk evening period could lead to a net reduction in fatal crashes. 3 When conducting a review of this literature, Aries and Newsham (2008) comment that "the results of prior investigations differ and are sometimes contradictory" (p. 1863). 4 Using data from Canada covering 1991-1992, Coren (1996 finds an increase in crashes on the first Monday of DST relative to the previous and subsequent Mondays.…”
mentioning
confidence: 99%
“…2 Since fatal crashes are more prevalent in the evening (online Appendix Figure A-1), it is possible that transferring light from a lower risk morning period to a higher risk evening period could lead to a net reduction in fatal crashes. 3 When conducting a review of this literature, Aries and Newsham (2008) comment that "the results of prior investigations differ and are sometimes contradictory" (p. 1863). 4 Using data from Canada covering 1991-1992, Coren (1996 finds an increase in crashes on the first Monday of DST relative to the previous and subsequent Mondays.…”
mentioning
confidence: 99%
“…In past times this was most probably true but there is no conclusive proof for it in modern times. Changed living and housing habits, air-conditioning and the mass usage of information and communication technologies (ICT) have eliminated or might even have reversed the energy saving effects (Aries & Newsham, 2008). There is no conclusive proof for any savings at all.…”
Section: International Discussionmentioning
confidence: 99%
“…Some countries, like the United Kingdom, even experimented with double summertime and year-round summertime. However, from March 1968 to October 1971, a trial was concluded with the notion that it would be impossible to quantify results and thus no position for or against was taken (Aries & Newsham, 2008).…”
Section: Historical Developmentmentioning
confidence: 99%
“…Natural light significantly influences both the balance of energy use in buildings and actual human activity [29][30][31], offering the occupants comfort and health benefits. The maximizing natural light penetration is one of the most important energy saving measures on the basis of independent on conventional energy.…”
Section: The Maximizing Natural Light Penetration Technologiesmentioning
confidence: 99%